2017
DOI: 10.1080/00223980.2017.1335687
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Instability Predicts Polymorphous Distress in Emerging Adults

Abstract: The primary aim of this investigation is to determine the extent to which transitional instability can predict diverse markers of distress in emerging adults. Participants were 210 emerging adults, aged 18-25 who completed measures of distress that included loneliness, stress, problem drinking, and prescription medication use. One year later, they returned to complete these same measures of distress along with a measure of significant life transitions that they encountered during the past year in such domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Whereas communication apprehensiveness is negatively associated with feeling like the college transition has a positive impact on one’s life (Dorrance Hall & Scharp, 2018), longitudinal investigations have found that students with higher social skills perform better academically (Furnham & Mitchell, 1991), have higher quality friendships (McKee, 2017), and experience less loneliness (Wei et al, 2005). Thus, similar to previous research that has found that socially skilled individuals are better able to solicit social support from others, social support is related to better psychosocial outcomes, and, taken together, social support is one mechanism that explains the association between social skills and psychosocial problems (e.g., Segrin et al, 2017), we predict that self-disclosure skills are directly associated with more positive and less negative psychosocial outcomes (H1) and with higher perceived social support (H2), perceived social support is directly associated with more positive and less negative psychosocial outcomes (H3) , and there is an indirect effect of social skills on psychosocial outcomes through social support (H4).…”
Section: Social Skills and Social Support During The Transition To Co...supporting
confidence: 82%
See 2 more Smart Citations
“…Whereas communication apprehensiveness is negatively associated with feeling like the college transition has a positive impact on one’s life (Dorrance Hall & Scharp, 2018), longitudinal investigations have found that students with higher social skills perform better academically (Furnham & Mitchell, 1991), have higher quality friendships (McKee, 2017), and experience less loneliness (Wei et al, 2005). Thus, similar to previous research that has found that socially skilled individuals are better able to solicit social support from others, social support is related to better psychosocial outcomes, and, taken together, social support is one mechanism that explains the association between social skills and psychosocial problems (e.g., Segrin et al, 2017), we predict that self-disclosure skills are directly associated with more positive and less negative psychosocial outcomes (H1) and with higher perceived social support (H2), perceived social support is directly associated with more positive and less negative psychosocial outcomes (H3) , and there is an indirect effect of social skills on psychosocial outcomes through social support (H4).…”
Section: Social Skills and Social Support During The Transition To Co...supporting
confidence: 82%
“…The advantages are not solely due to the possession of more appropriate and effective social skills; instead, part of the benefit is that the enactment and consequences of these behaviors are embedded within a relational context (e.g., Ryff & Singer, 2000). That is, more adequate social skills contribute to individuals’ ability to foster connections and positive relations with others, which subsequently allows them to experience improved psychological and social outcomes (Segrin & Taylor, 2007; Segrin et al, 2017). This process is particularly true in times of need, transition, and high stress, as the perception of social support from others can buffer the negative effects of distressing events on individuals’ well-being (Cohen & Wills, 1985; Segrin et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To this day, few longitudinal studies have examined the impact of instability experienced over long periods on emerging adults' adjustment. The results indicate that the frequency of transitions in multiple domains is linked to an increase in psychological distress (Segrin et al, 2017) and drug and alcohol use (Cadigan et al, 2021;Patrick et al, 2020). According to Patrick et al (2020), it seems that while the majority of emerging adults manage to adapt to the instability typical of this period, a certain threshold may exist where too many changes lead to more marked consequences for mental health and alcohol use.…”
Section: Accumulated Number Of Transitions Across Domainsmentioning
confidence: 99%
“…Emerging adults (ages 18-29), who are within a developmental period where social connection is of specific importance, are at a particular disadvantage during the COVID-19 pandemic. Even before the pandemic, research has suggested that they are particularly susceptible to feelings of loneliness and distress (Segrin et al, 2017). In general, EMC is a tool, that many emerging adults have used to socially connect with others (Herring, 1996).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%